Rare biogeochemical phenomenon associated to manganese patinas on mural painting and granite ashlars - Campos, Bruno (2021)
This article discloses a rare and outstanding type of Mn-rich black-blue patina found on mural painting and granite ashlars located in the church of Sta. Marinha, north of Portugal, and conjectures the phenomenon associated to the appearance of such patinas in different surface materials. This Mn-patina reported on mural painting and their origin is probably assigned to manganese leaching from building materials (i.e., granite and phyllites). Stained mural painting and granite examined by XPS and SEM have showed patinas enriched with manganese (IV) oxide, potentially catalysed by a microbiota, like fungi, observed in SEM micrographs. The pigments used to depict mural painting and groundwater were also analysed by micro-Raman and ICP-MS, respectively, indicating that they are unlikely manganese sources. Unstained building materials, such as granite ashlars, historic joints, mortars and phyllite rocks, were also analysed by ICP-MS showing that historic joints and mortars present significant concentrations of manganese, possibly associated to their absorbing feature. The main materials with potential to impart manganese to Mn-rich patinas are granite ashlars and phyllites. The aim of this investigation is to reveal and ascertain the hypothetical sources and the phenomenon responsible for the Mn-rich black-blue patina appearance, both on mural painting and granite ashlars.